An Analysis of Cohesive Devices in “The Drunk Text” Song by Henry Moodie - Diara April Hadiana; Zia Hisni Mubarak (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
The employment of cohesive devices in the lyrics of Henry Moodie's song "The Drunk Text" is examined in this research utilizing a qualitative descriptive technique, with an emphasis on how cohesion is created and how these devices support the text's unity and meaning. In order to detect cohesive techniques like reference, substitution, ellipsis, conjunction, and lexical cohesion, the official lyrics were gathered as data and analyzed using Halliday and Hasan's (1976) framework of cohesion. The results indicate that the most common mechanisms are lexical cohesiveness and reference, whereas replacement and ellipsis are less common. These unifying strategies are essential for connecting concepts, preserving thematic coherence, and boosting the lyrics' emotional expressiveness. This work advances the discipline of discourse analysis and offers a deeper knowledge of how cohesion functions in song lyrics as a kind of written discourse by applying cohesion theory to contemporary popular music texts.